MANHAJ TADRIS AL-ADAB AL-'ARABI LI GHAIR AL-'ARAB - Abukhudairi, Arif Karkhi (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2015)
The approaches  and methods are used in the teaching of Arabic literature in the Arab and non-Arab universities. The Orientalists drawer since the late nineteenth century exaggerate the formal side, and freeze history, and still today. Western professors studying Arabic literature in the light of traditional concepts fixed. The purpose of this research is to present and discuss methods of teaching Arabic literature at universities in Europe and the United States of America. The researcher uses in the study the descriptive and analytical and comparative, and reached a number of conclusions from the most important being that the teaching of literature should be based on a correct understanding of the meaning of literature firstly, a thorough knowledge of the characteristics of an Arab literature secondly, and a good choice of  odels that are placed in the hands of students thirdly. Moreover, it poses a researcher a new approach to the teaching of Arabic literature to non-Arab Arabic literature to non-Arab aims to literary taste the development of the students' non-Arab, and focused on the basic four areas namely linguistics, history, literary criticism, and comparative  literature.DOI: 10.15408/a.v2i2.2225